Lao People's Democratic Republic : Technical Assistance Report-Risk-Based Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2020)
The Banking Supervision Department (BSD) of the BoL is implementing risk-based supervision (RBS) methods. BoL staff are showing favorable results in understanding and applying RBS, recognizing that they are still in the early stages of capacity development. A new commercial banking law became effective in June 2019. The law incorporates expectations that financial institutions establish appropriate risk management systems and maintain adequate capital and liquidity. The law also gives the BoL purview over the adequacy of risk management in banks.